Egypt: Systematic analysis of world market and domestic production shocks - Mukashov, Askar; Diao, Xinshen; Ecker, Olivier; Jones, Eleanor; Thurlow, James (International Food Policy Research Institute, 2025)
This study is part of a series of country briefs by IFPRI that leverages economywide models to deliver detailed risk assessments of key economic indicators. This initial analysis evaluates vulnerabilities across economic sectors and key population groups to answer two questions: (1) How vulnerable are Egypt’s national economy and population to world market and domestic production shocks? (2) What are the largest risks to Egypt’s overall economic performance, private consumption, and reductions in poverty and undernourishment?